2022
DOI: 10.1139/apnm-2022-0165
|View full text |Cite
|
Sign up to set email alerts
|

The acute effect of maximal exercise on arterial stiffness in adults with and without intellectual and developmental disabilities

Abstract: Purpose: We compared central and peripheral arterial stiffness response patterns between persons with and without intellectual and developmental disabilities (IDD) of different age groups at rest and following a cardiopulmonary exercise test (CPET). Methods: 15 young adults with and without IDD, and 15 middle-aged adults without IDD performed a CPET. Central and peripheral arterial stiffness were measured at rest and following CPET using estimates of carotid-femoral (cfPWV), carotid-radial (crPWV), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Several past studies have reported the benefits of conventional exercise training in terms of aerobic training in improving the cardiovascular fitness and brachial systolic blood pressure in people with intellectual or developmental disabilities (16)(17)(18). However, the outcomes were varied and not conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Several past studies have reported the benefits of conventional exercise training in terms of aerobic training in improving the cardiovascular fitness and brachial systolic blood pressure in people with intellectual or developmental disabilities (16)(17)(18). However, the outcomes were varied and not conclusive.…”
Section: Discussionmentioning
confidence: 99%